2005
DOI: 10.1002/clc.4960281003
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in heart failure-A concise review

Abstract: Summary: Heart failure affects 5 million persons in the United States, with 400,000 new cases occurring every year. Paradoxically, although advances in coronary angioplasty and effective drugs have increased survival post infarction, the myocardial damage and subsequent neurohormonal activation-induced remodeling causes significant morbidity years later in the form of heart failure. Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) together with beta blockers modify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…У цьому контексті використання інгібіторів ангіотензин перетворюючого ферменту (ІАПФ) та блокаторів рецептора ангіотензину можуть перешкоджати синтезу еритропоетину та чутливості до нього кісткового мозку. Ще один механізм -при використанні ІАПФ підвищуються рівні N-ацетил-церил-аспартиллізин-проліну, який є інгібітором еритропоезу [32]. Наприклад, лікування еналаприлом було пов'язане з підвищенням ризику розвитку анемії на 56% через 1 рік після лікування [2].…”
Section: патогенез анемії та дефіциту заліза у пацієнтів із хронічною...unclassified
“…У цьому контексті використання інгібіторів ангіотензин перетворюючого ферменту (ІАПФ) та блокаторів рецептора ангіотензину можуть перешкоджати синтезу еритропоетину та чутливості до нього кісткового мозку. Ще один механізм -при використанні ІАПФ підвищуються рівні N-ацетил-церил-аспартиллізин-проліну, який є інгібітором еритропоезу [32]. Наприклад, лікування еналаприлом було пов'язане з підвищенням ризику розвитку анемії на 56% через 1 рік після лікування [2].…”
Section: патогенез анемії та дефіциту заліза у пацієнтів із хронічною...unclassified
“…For example, treatment with enalapril was associated to an intent-to-treat model, with a rise in the risk of developing new anemia at 1 year by 56% ( 17 ). The levels of N acetyl-seryl-aspartyl-lysin-prolyn, an erythropoiesis inhibitor, rise with ACEI usage, causing a fall in erythropoiesis and anemia ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] The levels of an erythropoiesis inhibitor, N-acetylseryl-aspartyl-lysin-prolyn, rise with the usage of ACE inhibitor, causing inhibition of erythropoiesis and manifestation of anemia. [ 19 ] A subanalysis of the PAERI study comparing 3,361 patients with diabetic kidney disease with 1,861 patients with non-diabetic CKD found that the diabetic patients were treated more often with ACE inhibitors (73.9 vs. 55.4%, P < 0.0001) and had a higher prevalence of anemia (52.7 vs. 39.4%, P < 0.0001). [ 20 ]…”
Section: Angiotensin-converting Enzyme Inhibitors and Its Relation With Anemiamentioning
confidence: 99%